2022
DOI: 10.1007/s00213-022-06077-w
|View full text |Cite
|
Sign up to set email alerts
|

L-DOPA administration shifts the stability-flexibility balance towards attentional capture by distractors during a visual search task

Abstract: Rationale The cognitive control dilemma describes the necessity to balance two antagonistic modes of attention: stability and flexibility. Stability refers to goal-directed thought, feeling, or action and flexibility refers to the complementary ability to adapt to an ever-changing environment. Their balance is thought to be maintained by neurotransmitters such as dopamine, most likely in a U-shaped rather than linear manner. However, in humans, studies on the stability-flexibility balance using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…Additionally, L-3,4-dihydroxyphenylalanine (L-DOPA), a DA precursor used as a medication in Parkinson's disease, produces alterations in latent inhibition (Polner et al, 2016;Gy€ orfi et al, 2017), even with only a single dose (Gy€ orfi et al, 2017), which signifies more attention allocated to irrelevant cues. This is unlikely to be a phenomenon specific to those with Parkinson's disease, as L-DOPA in healthy normals causes increases in attentional capture by distractors (Riedel et al, 2022). In contrast, DA depletion has been found to increase attentional control on the Stroop-Color Word task (Scholes et al, 2007), and, intriguingly, the same study also found these results with serotonin depletion.…”
Section: A Learning and Attention Filteringmentioning
confidence: 84%
“…Additionally, L-3,4-dihydroxyphenylalanine (L-DOPA), a DA precursor used as a medication in Parkinson's disease, produces alterations in latent inhibition (Polner et al, 2016;Gy€ orfi et al, 2017), even with only a single dose (Gy€ orfi et al, 2017), which signifies more attention allocated to irrelevant cues. This is unlikely to be a phenomenon specific to those with Parkinson's disease, as L-DOPA in healthy normals causes increases in attentional capture by distractors (Riedel et al, 2022). In contrast, DA depletion has been found to increase attentional control on the Stroop-Color Word task (Scholes et al, 2007), and, intriguingly, the same study also found these results with serotonin depletion.…”
Section: A Learning and Attention Filteringmentioning
confidence: 84%